Intersectoral interventions: integration for impact on preterm birth - Etienne V. Langlois; Maria El Bizri; Kelly Thompson; Amy Reid; Merette Khalil; Giulia Gasparri; Joy E. Lawn; Teesta Dey; Judith Robb-McCord; Yousra-Imane Benaskeur; Ana Bonell; Amanuel Gidebo; et al. (Reproductive Health)
Abstract Progress The last two decades have seen a growing focus on intersectoral interventions to improve maternal and newborn health and well-being outcomes, as reflected in efforts to achieve the Millennium Development Goals (MDGs) and advance the Sustainable Development Goals (SDGs). Preterm births are linked to cross-sectoral determinants that affect health outcomes and human capital across the life-course, necessitating an intersectoral approach that addresses these multifaceted challenges. Programmatic priorities Recognizing that social, biological and economic determinants significantly influence health outcomes, it is critical that robust health systems are reinforced by a comprehensive intersectoral approach. Evidence suggests that the factors influencing preterm birth, and the health of small and sick newborns are vast and varied, requiring interventions that address equity and rights, education, economic factors, environmental conditions, and emergency responses, i.e., a new framework entitled "five Es". Pivots Improving outcomes for newborns, including preterm and small for gestational age babies, and preventing stillbirths, requires enhanced measurement and accountability within intersectoral programs across the 'five Es'. Investment in equity-focused, gender-transformative, and rights-based policies and programs across various sectors is crucial. Priority areas include ensuring equitable and inclusive education, particularly comprehensive sexual and reproductive health education; developing innovative financing schemes that protect and support families with complicated pregnancies and vulnerable infants; creating environmentally adaptive systems that prioritize maternal and newborn health; and implementing emergency response plans that guarantee the continuity of maternal and newborn health services. Evidence-based intersectoral interventions offer a promising pathway to reducing preterm births and improving health outcomes across generations. By addressing the five Es, intersectoral interventions can create a healthier future for preterm babies, children, adolescents, women, and society as a whole.